SEG Technical Program Expanded Abstracts 2002 2002
DOI: 10.1190/1.1817354
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic noise reduction opens the way for array size reduction in vibroseis™ operations

Abstract: To compensate for the reduced number of vibrators per shot point required by reductions in group interval and array size, either the recording time per surface unit must be increased or high order simultaneous recording techniques such as the slip sweep technique should be used. Yet these techniques suffer from distortion, which contaminates the data in proportion to the productivity increase generated. A method to significantly reduce this contamination is presented. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 1 publication
(2 reference statements)
0
23
0
Order By: Relevance
“…At the 2006 EAGE conference, C. Bagaini (3) compared several of these techniques. Harmonic noise reduction was indeed proposed in 2002 by Meunier & Bianchi (5) . At the 2002 EAGE conference, T. Bianchi (4) presented an experiment where various simultaneous acquisition techniques were compared.…”
Section: Increasing Vibroseis Source Density With Acceptable Costmentioning
confidence: 91%
See 1 more Smart Citation
“…At the 2006 EAGE conference, C. Bagaini (3) compared several of these techniques. Harmonic noise reduction was indeed proposed in 2002 by Meunier & Bianchi (5) . At the 2002 EAGE conference, T. Bianchi (4) presented an experiment where various simultaneous acquisition techniques were compared.…”
Section: Increasing Vibroseis Source Density With Acceptable Costmentioning
confidence: 91%
“…This process consists in harmonic noise estimation using the recorded force and in its subsequent subtraction from the data (5) . This process consists in harmonic noise estimation using the recorded force and in its subsequent subtraction from the data (5) .…”
Section: Figure 4: Single Vibrator Record After Harmonic Noise Reductionmentioning
confidence: 99%
“…The Sorkin technique depends on phase difference between consecutive sweeps. Meunier and Bianchi (2002) proposed a technique to significantly reduce harmonic contamination in raw data from slip sweep acquisition. It can be demonstrated that harmonics up to M th order are suppressed (in this case the 2 nd harmonic actually corresponds to twice the fundamental).…”
Section: T E C H N I Q U E S U S E D F O R I M P R O V I N G V I B R mentioning
confidence: 99%
“…To improve the vibroseis data quality via numerical simulation, a procedure that is based on the previous work of Jeffryes (2002) and Meunier and Bianchi (2002) was proposed by Abd El-Aal (2010). This noise is of two types: environmental noise and source-generated noise.…”
Section: H a R M O N I C B Y H A R M O N I C A T T E N U A T I O N P mentioning
confidence: 99%
“…Jeng (geofv001@ntnu.edu.tw) results of signal distortions and artifacts generated. Subtracting an estimate of the harmonic noise from the recorded data is the current main approach (Nyman and Gaiser, 1983;Butler and Russell, 1993;Jeffryes, 2002;Meunier and Bianchi, 2002;Butler and Russell, 2003;Saucier et al, 2006). The estimate includes the estimating of harmonic noise fundamental frequency, and amplitudes and phases of all harmonics.…”
Section: Introductionmentioning
confidence: 99%